Multi-sectoral taskforce model on food safety - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
The task force model was successfully supported by ILRI in Vietnam. Now being adapted for Cambodia. A design workshop was held in October 2018; the task force was officially launched in 2019. Previously reported as stage 4, but as model is untested for Cambodia, moved to innovation/stage 1.